Front Cover: Impedance‐based viscoelastic flow cytometry. Issue 6 (12th March 2019) - Serhatlioglu, Murat; Asghari, Mohammad; Tahsin Guler, Mustafa; Elbuken, Caglar
Abstract : DOI:10.1002/elps.201800365 The cover picture shows viscoelastic focusing of human red blood cells in parachute‐shape orientation suspended in a polyethylene oxide solution (500 ppm, 5MDa in 1X PBS). Impedimetric detection of cells was achieved with very low signal variability thanks to the alignment of these non‐spherical cells in a single, axially symmetric, orientation along the flow direction. For cytometry applications, weak polyelectrolyte viscoelastic solutions can be used to obtain the rheological properties required for viscoelastic focusing while allowing the ionic concentration optimization for impedimetric signal detection.